Structure based designing of thiazolidinone-pyrimidine derivatives as ERK2 inhibitors: Synthesis and in vitro evaluation. Issue 10 (3rd October 2021) - Pathania, S.; Singh, P.K.; Narang, R.K.; Rawal, R.K.
ABSTRACT: Breast cancer has been associated with an overexpression of various molecular targets; accordingly, various target-specific chemotherapeutic agents have been developed. Inhibition of ERK2, a member of MAPK pathway, is an important target involved in the treatment of both oestrogen receptor-positive and triple-negative breast cancer. Thus, in continuation of our previous work on the ERK2 target, we here report novel inhibitors of this kinase. Out of three lead molecules reported in our previous study, we selected the thiazolidinone-pyrimidine scaffold for further development of small molecule inhibitors of ERK2. Analogues of the lead molecule were docked in the target kinase, followed by molecular dynamic simulations and MM-GBSA calculations. Analogues maintaining key interactions with amino acid residues in the ATP-binding domain of ERK2 were selected and duly synthesized. In vitro biochemical evaluation of these molecules against ERK2 kinase disclosed that two molecules possess significant kinase inhibitory potential with IC50 values ≤ 0.5 µM.